Perilaku Pengguna dalam Memberikan Komentar Jahat di Media Sosial: Studi pada Pengguna Tiktok dan Instagram - Wilona Ramadhani K; Muhammad Irwan Padli Nasution (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
This study aims to describe users' experiences and perceptions regarding the presence of malicious comments on social media, particularly on TikTok and Instagram. Data were collected through an online questionnaire using Google Forms containing eight open-ended questions, then analyzed using a descriptive qualitative approach through thematic analysis. The results showed that all respondents had and frequently encountered malicious comments, especially on viral content or creator accounts with large followings. The most common forms of malicious comments included body shaming, insults, defamation, and belittling and demeaning comments. Respondents expressed various emotional reactions such as discomfort, sadness, anger, and pity, although a small number felt normal due to their familiarity with the phenomenon. Factors that drive someone to make malicious comments include following the crowd (FOMO), envy, personal dislike, and the ease of expressing negative opinions on social media. Malicious comments also impact user comfort, with most feeling disturbed and uncomfortable. Respondents' responses to malicious comments included ignoring, responding positively to reprimands, blocking accounts, or reporting the comments. Respondents also proposed several efforts to reduce malicious comments, such as limiting or closing the comment section and increasing education regarding social media ethics. Overall, this study confirms that malicious comments are a common phenomenon on social media and need to be addressed through better personal awareness and digital literacy.